2020
DOI: 10.18684/bsaa(18)135-144
|View full text |Cite
|
Sign up to set email alerts
|

Efecto del periodo de recuperación en la producción y calidad nutricional de algunas especies forrajeras

Abstract: Historial del ArtículoRecibido para evaluación: 12 de Septiembre 2019. Aprobado para publicación: 4 de Mayo 2020.* Proyecto de investigación de orígen: "Evaluación de la respuesta agronómica de algunas especies forrajeras de trópico alto como estrategia hacia una ganadería ecoeficiente".

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 25 publications
(45 reference statements)
2
3
0
3
Order By: Relevance
“…In turn, Valles-de la Mora et al (2017) reported lower fibre contents in the association Toledo with C. argentea compared to Toledo alone. The same effect has been found in temperate zones, where Tripholium spp has positively influenced the nutritional quality of forage grasses (Fonseca-López et al, 2020). In the case of the association of Mulato II with C. brasiliensis, it only showed an effect on PC content.…”
Section: Forage Qualitysupporting
confidence: 69%
See 1 more Smart Citation
“…In turn, Valles-de la Mora et al (2017) reported lower fibre contents in the association Toledo with C. argentea compared to Toledo alone. The same effect has been found in temperate zones, where Tripholium spp has positively influenced the nutritional quality of forage grasses (Fonseca-López et al, 2020). In the case of the association of Mulato II with C. brasiliensis, it only showed an effect on PC content.…”
Section: Forage Qualitysupporting
confidence: 69%
“…This would allow the legume to develop better and contribute more biomass to the system, in addition to directly favoured nitrogen fixation, since dry matter production also depends on nitrogen (Lüscher et al, 2014). This behaviour is reported for forages from temperate zones, where Tripholium spp, influences on biomass production (green and dry) of forage grasses (Fonseca-López et al, 2020).…”
Section: Results and Discussion Vigour Height Coverage And Presence O...mentioning
confidence: 67%
“…As shown in Figure 1, sampling was carried out by selecting three coffee plots (twelve coffee plants in each plot) under three different coverings: banana trees (CP), mandarin trees (CM), and three citrus fruit trees (CC) (mandarin, lemon, and orange). The EA techniques applied were: 1) worm humus (Californian earthworm) (Milanés et al, 2005); 2) biofertilizer, obtained from the mixture of legumes, molasses, yeast, chicha, poultry manure, rabbit manure, wood ash, and milk (Trejo-Escareño et al, 2013); 3) efficient microorganisms (EM) from a mix of leaf litter, rice grits, molasses, and milk (Callisaya & Fernández, 2017); 4) poultry manure (González et al, 2013); 5) Red clover green manures (Trifolium pratense) (Fonseca-López et al, 2020); and 6) cover crops b. Moisture (gravimetric method): it consists of taking a soil sample, weighing it before and after drying, and calculating its moisture content. The soil sample is considered to be dry when its weight remains constant at a temperature of 105 ºC (IDEAM, 1994).…”
Section: Experimental Design and Soil Samplingmentioning
confidence: 99%
“…Entre las especies forrajeras en las que se han usado aguas residuales para riego, se encuentran los pastos de corte (Fonseca et al 2020), que se destacan por fácil adaptación a las condiciones de trópico seco (Martínez et al 2020;Murillo et al 2014). Una de las especies forrajeras más utilizadas en el caribe colombiano es el pasto King Grass, el cual, es un híbrido natural entre Pennisetum purpureum y P. typhoides (Martínez & González, 2017).…”
Section: Introductionunclassified
“…Una de las especies forrajeras más utilizadas en el caribe colombiano es el pasto King Grass, el cual, es un híbrido natural entre Pennisetum purpureum y P. typhoides (Martínez & González, 2017). Este pasto fue ampliamente evaluado en la década de los 70 y parte de los 80 (Fonseca et al 2020).…”
Section: Introductionunclassified